2011
DOI: 10.2298/bah1103687g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of betaine and air ammonia concentration on broiler performance, plasma corticosterone level, lymphoid organ weights and some haematological indices

Abstract: This study was initiated to examine the effect of betaine supplementation (1g/kg) on hematocrit level, erythrocyte and leukocyte number, heterophil/lymphocyte ratio, plasma corticosterone, rectal temperature, relative lymphoid organ weights and average daily gain in broiler chickens reared in a poultry house under natural ambient conditions and high air ammonia level. A total of 100 broiler chickens at the age of 45 d were allocated into 2 groups: control and betaine supplemented. The broiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
10
0
4
Order By: Relevance
“…On the other hand, Attia et al (2005), based on the study of the ratio of added methionine and betaine in nutrition of slow growing chickens, reported that successful substitution of methionine with betaine is possible. Other researchers (Matthews and Southern, 2000;Hassan et al, 2005;Gudev et al, 2011) have indicated that in certain conditions, adding of betaine into the feed resulted in improvement of one or several parameters of productivity, primarily daily gain, feed conversion ratio and resistance of broilers. However, other studies report of minimum or no effect at all of betaine supplementation on performance of fattening poultry (Rostagno and Pack, 1996;Zulkifli et al, 2004).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, Attia et al (2005), based on the study of the ratio of added methionine and betaine in nutrition of slow growing chickens, reported that successful substitution of methionine with betaine is possible. Other researchers (Matthews and Southern, 2000;Hassan et al, 2005;Gudev et al, 2011) have indicated that in certain conditions, adding of betaine into the feed resulted in improvement of one or several parameters of productivity, primarily daily gain, feed conversion ratio and resistance of broilers. However, other studies report of minimum or no effect at all of betaine supplementation on performance of fattening poultry (Rostagno and Pack, 1996;Zulkifli et al, 2004).…”
Section: Resultsmentioning
confidence: 98%
“…Role of betaine as osmotic-regulator in the organism occurs at the cellular level where betaine acts as osmolyte and minimizes the loss of water from the cell, which can be of special importance in conditions of stress and dehydration of the organism caused by disease or high temperature (Matthews and Southern, 2000;Zulkifli et al,2004;Gudev et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menurut Emadi et al (2007) nilai konstan heterofil/limfosit adalah berada dikisaran 0,2-0,8 dengan nilai normal 0,5. Peningkatan nilai H/L disebabkan oleh peningkatan hormon stres yang disekresikan oleh kelenjar adrenal (Gudev et al, 2011), maka nilai H/L yang meningkat merupakan indikasi stres yang meningkat pula (Cetin et al, 2011). Peningkatan nilai H/L darah menunjukkan pula peningkatan pada hormon glukokortikoid dalam kondisi cekaman panas (Davis et al, 2008).…”
Section: Polimorfisme Gen Hsp70unclassified
“…Rasio N/L merupakan indikator adanya stres. Altan et al (2000) menyatakan bahwa stress menyebabkan rasio N/L meningkat hal ini disebabkan hormon yang meningkatkan stres disekresikan oleh kelenjar adrenal akan meningkatkan rasio N/L Gudev et al (2011). Penelitian ini menunjukkan domba dengan pemeliharaan semi intensif maupun intensif dengan pemberian konsentrat yang berbeda memiliki rasio N/L yang normal sesuai dengan pendapat Kannan et al (2000) bahwa nilai normal rasio N/L pada domba yaitu sebesar 1,5%.…”
Section: Rasio Neutrofil/limfosit (Rasio N/l)unclassified